The effect of montelukast, a leukotriene receptor antagonist, on the acetic acid-induced model of colitis in rats: Involvement of NO-cGMP-KATP channels pathway - Ghorbanzadeh, Behnam; Behmanesh, Mohammad Amin; Mahmoudinejad, Roya; Zamaniyan, Mehdi; Ekhtiar, Shadi; Paridar, Yousef (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease is a chronic autoimmune disorder that may involve entire gastrointestinal tract. The leukotrienes have a role as mediators in the pathophysiology of colitis. Here, we investigated the effect of a leukotriene receptor antagonist, montelukast, and also the role of the NO-cGMP-KATP channel pathway in acetic acid-induced colitis. Rectal administration of acetic acid (4%) was used for induction of colitis in rats. To investigate our hypothesis, the rats were intraperitoneally pre-treated with L-NAME (NOS inhibitor), L-arginine, sildenafil, methylene blue, glibenclamide, or diazoxide 15 min before treatment with montelukast (5-20 mg/kg, i.p.), for 3 consecutive days. Then, microscopic, macroscopic, and inflammatory parameters were evaluated. Montelukast reduced the microscopic and macroscopic damage induced by acetic acid. Montelukast also reduced the level of IL-1β and TNF-α. We also showed that the effects of montelukast were significantly attenuated by L-NAME, methylene blue (guanylate cyclase inhibitor), and an ATP-sensitive potassium channel blocker (glibenclamide). Also, the administration of L-arginine, sildenafil, and diazoxide before montelukast produced protective effect. In conclusion, the pathway of the NO-cGMP-KATP channel is involved in the protective effect of montelukast in acetic acid-induced colonic tissue damage